Svistunov A. S. Empirical radio wave propagation models for analysis of intrasystem electromagnetic compatibility and safety of microcellular communication networks - Svistunov, Alexander S. (Journal of the Belarusian State University. Physics, 2019)
The possibility to use the empirical radio-wave propagation models for diagnostics of intrasystem electromagnetic compatibility and electromagnetic safety of microcellular radio networks in the urban area is analyzed. The paper presents comparative results of signal levels received by mobile stations at distances from base station of less than 1 km estimated using the three-dimensional multibeam radio wave propagation model (X3D model), with regard to a three-dimensional model for the fragment of a typical urban area with buildings 6–20 m high, and using the well known radio wave propagation empirical models. Comparison was made with the use of the «Mean error» and «Standard deviation» criteria. Based on the results obtained, it is concluded that the COST231 – Hata model or the Ibrahim – Parsons model may be recommended for diagnostics of intrasystem electromagnetic compatibility and for analysis of electromagnetic safety of microcellular radio networks due to high quality of service in cellular communications because the estimates of signal levels with their use correlate closely with the results obtained using X3D model for the considered urban area. The Okumura – Hata, COST231 – Hata, Ibrahim – Parsons models can be applied for the base – mobile station distances of 0.4 –1.0 km.
Keywords: intrasystem electromagnetic compatibility; cellular radio network; base stations; electromagnetic safety; radio wave propagation models